Winners and losers from COVID-19: Global evidence from Google search - Abay, Kibrom A.; Tafere, Kibrom; Woldemichael, Andinet (World Bank, 2020)
As COVID-19 continues to wreak havoc across the world, researchers are attempting to quantify the economic fallout from the pandemic as it continues to unfold. Estimating the economic impacts of a prevailing pandemic is fraught with uncertainties about the epidemiology of the disease and the breadth of disruption of economic activities. This paper employs historical and near real-time Google search data to estimate the immediate impacts of COVID-19 on demand for selected services across 182 countries. The analysis exploits the temporal and spatial variations in the spread of the virus and finds that demand for services that require face-to-face interaction, such as hotels, restaurants and retail trade, has substantially contracted. In contrast, demand for services that can be performed remotely or provide solutions to the challenges of reduced personal interactions, such as information and communications technology (ICT), and deliveries, has increased significantly. In a span of three months, the pandemic has resulted in a 63 percent reduction in demand for hotels, while increasing demand for ICT by a comparable rate. The impacts appear to be driven by supply contractions, due to social distancing and lockdown measures, and demand shocks as consumers shelter in place, with the latter dominating for most services. The magnitude of the changes in demand varies considerably with government responses to the pandemic.